Analysis of surgery rates among 25 national collegiate athletic association sports - Taree, A.; Charen, D.; Huang, H.-H.; Poeran, J.; Colvin, A. (The Physician and Sportsmedicine, 2022)
Objectives While injuries among collegiate athletes are common and well-studied, there have been no studies comparing which sports and injury types have the highest operation rates. This information would be valuable for athlete governing bodies and providers to improve player safety. Our hypothesis was the surgery incidence rates vary substantially between sports and injury types, with football and knee injuries representing the sport and injury type with the highest respective surgery rates.